NetBeans™ Ruby and Rails IDE with JRuby - Kutler, Chris (Apress, 2012)
As you gain experience with the NetBeans IDE, you come to learn that it appears to be endlessly customizable. The NetBeans editor allows you to customize code folding, code completion, formatting, templates, hints, fonts, colors, and task list patterns, as well as record your favorite actions as macros. The existing keyboard shortcuts are all configurable, and you can easily define new ones to match your favorite actions. NetBeans™ Ruby and Rails IDE with JRuby 175 The templates that define each new file are also easily accessible and configurable, including the license that appears in your code. In addition, it is possible to change how project files are displayed, which project files are displayed, and their default locations. Finally, this chapter concludes with a sampling of some of the "under the hood" options you can use to really fine tune and understand how the NetBeans IDE is working for you.